2003
DOI: 10.1016/s1074-7613(03)00025-6
|View full text |Cite
|
Sign up to set email alerts
|

Loss of TACI Causes Fatal Lymphoproliferation and Autoimmunity, Establishing TACI as an Inhibitory BLyS Receptor

Abstract: BLys , a key cytokine that sustains B cell maturation and tolerance, binds three receptors: BR3, BCMA, and TACI. Results from knockout mice implicate a major functional role for BR3 and a redundant one for BCMA in B cell function. TACI's role is controversial based on defects in TI antibody responses accompanied by B cell hyperplasia in knockout mice. We have presently characterized a precise role for TACI in vivo. TACI(-/-) mice develop fatal autoimmune glomerulonephritis, proteinurea, and elevated levels of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
322
0
6

Year Published

2003
2003
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 365 publications
(335 citation statements)
references
References 39 publications
7
322
0
6
Order By: Relevance
“…Accordingly, we found that APRIL, which signals through TACI but not through BAFF-R, does not promote Fas killing of LPS-activated B cells. Our data suggest that the model that TACI is a negative regulator of B cells, while BAFF-R is a positive regulator [39], may not always be the case since the effect of TACI or BAFF-R signaling depends on the context in which the B cell is signaled through these receptors. We also demonstrated that coupling of BAFF and LPS signaling induces an inhibition of the MEK/ERK pathway that may be responsible for Fas up-regulation.…”
Section: Discussionmentioning
confidence: 82%
“…Accordingly, we found that APRIL, which signals through TACI but not through BAFF-R, does not promote Fas killing of LPS-activated B cells. Our data suggest that the model that TACI is a negative regulator of B cells, while BAFF-R is a positive regulator [39], may not always be the case since the effect of TACI or BAFF-R signaling depends on the context in which the B cell is signaled through these receptors. We also demonstrated that coupling of BAFF and LPS signaling induces an inhibition of the MEK/ERK pathway that may be responsible for Fas up-regulation.…”
Section: Discussionmentioning
confidence: 82%
“…Several TACI knockout, transgenic, and knock-in mouse models have been generated. Some of them develop lymphoproliferative disorders, splenomegaly, and severe SLE-like autoimmune disorders with premature death due to renal failure (34,35). These data from animal models suggest that in addition to its role in B cell activation, TACI plays an inhibitory role in lymphocyte homeostasis.…”
Section: Genetics Of Cvidmentioning
confidence: 98%
“…The other two receptors, transmembrane activator calcium modulator and cyclophilin ligand interactor (TACI) and B cell maturation Ag (BCMA), can bind both BLyS and a proliferation-inducing ligand (APRIL), and affinity measurements suggest that APRIL may be their physiologically relevant ligand. Mice lacking TACI have elevated B cell numbers (22,23), suggesting a potential negative regulatory role for this receptor, whereas BCMA appears to be involved in the control of plasmacytes, rather than mature resting B cells (24). In addition, TACI knockout mice display defective T cell-independent type II responses, further suggesting that TACI and BCMA may be involved in regulating the behavior of activated B cells.…”
Section: Tlr Stimulation Modifies Blys Receptor Expression Inmentioning
confidence: 99%